Use of virtual reality in residential estate marketing toward house purchasing intention - Azmi, Athira (2021)
The provision of adequate housing is one of the key Malaysian government agenda for the growth and well-being of society. Despite the government 's endeavours to provide sufficient, affordable, and quality housing, research has found that this form of housing has not been satisfactory in terms of the living environtment among its inhabitants. The lack of study on homebuyers' emotion and behaviour within the housing industry motivates this research. This study believes in the potentials of virtual reality technology for facilitating home purchase decisions as part of the marketing tool in the residential real estate industry. This study reviewed extensive literature focusing on the role of emotions in homeownership, consumer behaviours and virtual reality applications in marketing. This study proposed that the atmospheric evaluation, perceived emotional values, perceived usefulness and perceived ease of use are the stimuli that could influence pleasure, arousal and satisfaction emotions, which in turn, could influence home purchase intentions in the virtual environment. In this study, an experiment was conducted to determine whether virtual reality could be an adequate representation of the real environment for potential homebuyers to evaluate housing choices. The relationships between the proposed stimuli components, their effect on emotional states and purchase intention was assessed using Partial Least Squares- Structural Equation Modelling. Results indicated that there is a significant difference in the atmospheric evaluations, perceived emotional values, perceived usefulness, perceived ease of use, satisfaction and purchase intention between the real environment and the virtual environment. Only the pleasure and arousal emotions evoked in the real and virtual environment have no significant differences. Statistical analysis also revealed that atmospheric evaluations significantly and positively affect pleasure and arousal emotions. Perceived usefulness and perceived ease of use both have a significant positive effect on satisfaction. Pleasure and satisfaction were found to positively influence home purchase intention. Based on the findings, this study highlights the recommendations to enhance the application of virtual reality to be strategically applied in the residential real estate marketing for facilitating emotional experience and home evaluation. This study also serves as a benchmark for future studies in residential estate marketing using virtual reality focusing on users' emotion and behaviour.